PWE-184 The Association of Dietician follow up with the Quality of Life in Coeliac Disease. (4th June 2013) - Zubir, M A; Engel, B
Abstract : Introduction: Coeliac disease (CD) is present in 1% of the UK population however there are still many undiagnosed cases in the community. The main treatment for this condition is gluten free diet. The role of dieticians in the follow up care of CD patients is crucial especially with regards to educating CD patients about their dietary requirement as well as their role in disease monitoring. The aim of the study is to assess the association of dieticians follow up on the quality of life in CD patients. Methods: CD patients who were identified on histology over a 10 years period in East Sussex were sent a socio-demographic questionnaire and the Coeliac Disease Quality of Life (CD-QOL) survey by post. The participants of the study who attend dietician follow up were then compared with those who did not. Multiple linear and logistic regression analyses were used to identify any significant relationships Results: Overall, 58 participants (34%) completed and returned the questionnaires. Dietician involvement appeared to be the most important predictor (beta = –0.424, p = 0.001) for overall CDQOL score but surprisingly, the negative value indicates that dietician involvement was associated with a lower quality of life score. Increasing age seemed to have a positive impact (beta = 0.312, p = 0.011) on overall quality of life. However, a change of the recent gluten free prescription (beta = –0.246, p = 0.037) which limits the products available and having initially presented with gastrointestinal symptoms (beta = –0.24, p = 0.044) were found to have negative contributions to the overall CDQOL score. The overall model fit was moderate (R2 = 0.336). Logistic regression was used to identify the likelihood of dietician follow up and the only significant predictor identified was the overall CDQOL score (OR 0.95, p = 0.019) which indicates that those with higher quality of life score were less likely to have dietician follow up. Conclusion: Dietician follow up is associated with poorer quality of life but due to the nature of this study, cause and effect cannot be established. It may be that patients who have poorer quality of life chose to see a dietician and longitudinal study is required to further assess this association. This study also suggests that the recent change to the gluten free prescription has negatively impacted the quality of life of those with CD. This fact should be taken into consideration for any future health providers dealing with local CD service provisions. Disclosure of Interest: None Declared.